On the External Failure Surface in PSEs: Numerical and Theoretical Methods - Jiaqing Liu; Zeyu Xu; Shuai Zhou (Advances in Civil Engineering)
The evolution of soil arching, involving internal and external failure surfaces, is of significance to the load transfer mechanism of pile-supported embankments (PSEs), and external failure surfaces are generally observed in cases of greater embankment height. In this study, the evolution of external failure surfaces was investigated by both numerical and theoretical methods. To begin with, numerical simulations of trapdoor tests were carried out by a two-dimensional discrete element method. The influences of two key parameters (i.e., embankment height and net spacing between piles) on the development of external failure surfaces were emphasized. The measured coefficient of lateral earth pressure around the external failure surface was close to the predicted coefficient of active earth pressure. Then, a theoretical solution considering inclined external failure surfaces, more realistic compared to those adopted in Terzaghi’s method, was proposed. Compared with Terzaghi’s method, the proposed solution exhibited better consistency with laboratory observations, especially when external failure surfaces were significantly observed.